2008
DOI: 10.1016/j.watres.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic oxidation of arsenite linked to denitrification in sludges and sediments

Abstract: In this study, denitrification linked to the oxidation of arsenite (As(III)) to arsenate (As(V)) was shown to be a widespread microbial activity in anaerobic sludge and sediment samples that were not previously exposed to arsenic contamination. When incubated with 0.5 mM As(III) and 10 mM NO 3 − , the anoxic oxidation of As(III) commenced within a few days, achieving specific activities of up to 1.24 mmol As(V) formed g −1 volatile suspended solids d −1 due to growth (doubling times of 0.74 to 1.4 d). The anox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Recently, several studies have demonstrated that nitrate-dependent As(III) oxidation is carried out by anaerobic microorganisms to gain energy from As(III) oxidation. As(III)-oxidizing denitrifying bacteria have been isolated from various environments including As-contaminated lakes and soil (21,25), as well as enrichment cultures (ECs), and isolates from pristine sediments and sludge samples (33,34). 16S rRNA gene clone library characterization of the ECs indicates that the predominant phylotypes were from the genus Azoarcus and the family Comamonadaceae (34).…”
mentioning
confidence: 99%
“…Recently, several studies have demonstrated that nitrate-dependent As(III) oxidation is carried out by anaerobic microorganisms to gain energy from As(III) oxidation. As(III)-oxidizing denitrifying bacteria have been isolated from various environments including As-contaminated lakes and soil (21,25), as well as enrichment cultures (ECs), and isolates from pristine sediments and sludge samples (33,34). 16S rRNA gene clone library characterization of the ECs indicates that the predominant phylotypes were from the genus Azoarcus and the family Comamonadaceae (34).…”
mentioning
confidence: 99%
“…Equilibrium Equation (2.6-2.7) shows that H2AsO3 -anion is dominant in basic or slightly acidic solution whiles the HAsO3 2-dominate in basic solution (Wagman et al, 1968). The biochemistry of arsenic species has also been demonstrated by researchers (Wang et al, 2013;Sun et al, 2010;Aniruddha and Wang, 2010;Sun et al, 2008). Aniruddha and Wang, (2010) reported that As(III) can be oxidised to As(V) in the presence of oxidizing agent by donating 2 electrons, while generating a considerable amount of energy for cell growth and metabolism Equation (2.8).…”
Section: Chromium Co-pollutant (As)mentioning
confidence: 82%
“…to As(V) under both aerobic and anaerobic conditions have been investigated (Aniruddha and Wang, 2010;Sun et al, 2010;Sun et al, 2008). The first heterotrophic As(III) oxidizing bacteria was described by (Green 1918), whereas an autotrophic As(III) oxidizing strain, − 17 − Pseudomonas arsenitoxidans, was first reported in 1981 (Ilialetdinov and Abdrashitova 1981).…”
Section: Microbial Oxidation Of As(iii) To As(v)mentioning
confidence: 99%
See 2 more Smart Citations